RETHINKING EDUCATIONAL MANAGERIALISM: A CRITICAL PARADIGM AS AN EPISTEMOLOGICAL COUNTERBALANCE IN CONTEMPORARY EDUCATION - Supriyadi Supriyadi; Nuryati Nuryati; Nurul Dewi hayati; Masitoh Masitoh; Siti Nur Asiah (El Midad, 2026)
The growing dominance of educational managerialism in contemporary education has reshaped governance practices by emphasizing efficiency, accountability, standardization, and performance measurement. While managerial approaches have contributed to administrative order and organizational control, they are increasingly criticized for narrowing the epistemological and ethical foundations of education. This study aims to examine educational managerialism as a critical epistemological paradigm and to position the critical paradigm as an epistemological counterbalance within contemporary education. Employing a qualitative critical literature review, this study analyzes peer-reviewed journal articles and scholarly books published between 2020 and 2024 using a critical epistemological framework informed by critical social theory. The analysis focuses on uncovering the epistemological assumptions, ideological orientations, and power relations embedded in managerial knowledge and governance practices. The findings reveal that educational managerialism privileges instrumental rationality and claims of value neutrality, which function to legitimize performance-based governance while marginalizing reflective, ethical, and contextual forms of educational knowledge. In contrast, the critical paradigm offers a reflective framework that challenges these assumptions and reorients educational management toward democratic participation, social justice, and human emancipation. Rather than rejecting management outright, this study demonstrates that the critical paradigm can function as a corrective and balancing epistemological framework, enabling more humanistic and ethically grounded approaches to educational governance. This article contributes to international debates on critical educational management by advancing an epistemological synthesis that integrates critique with constructive transformation.